Elaboration of the Concept of Serious Human Rights Violations in Indonesia: Jus Cogens in the Framework of Corporations Criminal Responsibility - Adhryansyah; Prihandono, Iman; Rachman, Taufik (Universitas Airlangga, 2025)
The handling of serious human rights violations committed by corporations in Indonesia remains legally and practically uncertain, particularly regarding the recognition of corporations as subjects of international human rights law. This issue has become increasingly urgent, as some corporations with strong financial influence are able to pursue profit at the expense of fundamental human rights, often without facing adequate legal consequences. The lack of a clear and enforceable framework for holding corporations criminally accountable risks enabling impunity and undermining justice for victims. This research aims to address that gap by developing a legal concept of corporate criminal responsibility specifically for gross human rights violations, tailored to the Indonesian context. The study adopts a statutory, conceptual, and case-based approach to explore how corporate liability can be effectively integrated into the national criminal justice system. It also emphasizes the need for harmonization between Law Number 26 of 2000 on Human Rights Courts and Law Number 1 of 2023 on the Criminal Code, in order to ensure legal coherence and uphold jus cogens norms—universal principles of international law that prohibit severe human rights abuses such as genocide, torture, and crimes against humanity. By proposing a structured approach to corporate accountability, this research seeks to strengthen Indonesia’s legal capacity to respond to serious human rights violations and contribute to the broader goal of promoting justice and the rule of law.